Antisocial Personality Disorder Comorbidity in Methamphetamine Use Disorder: Sociodemographic, clinical and childhood trauma correlates - Rall, Edrich (Department of Psychology, 2021)
Personality pathology, especially antisocial personality disorder (ASPD), often occurs in patients with methamphetamine use disorder (MAUD). However, little is known about potential risk factors for this dual diagnosis, and the impact of this comorbidity on both the severity of MAUD and levels of functional impairment. Casting light on such phenomena may aid in early identification of treatment targets, assist in the management of patients in this particular population, and contribute to development of treatment strategies. This crosssectional study described and compared sociodemographic, clinical and childhood trauma correlates in patients with a dual diagnosis of MAUD and ASPD (MAUD+ASPD) and those with MAUD without ASPD (MAUD-ASPD). The contribution of sociodemographic and childhood trauma variables in predicting membership of the MAUD+ASPD group was also investigated. A sample of 62 adult patients with a primary diagnosis of MAUD took part in the study. A sociodemographic questionnaire was completed and well established diagnostic measures of ASPD (The Mini-International Neuropsychiatric Interview; MINI) and MAUD (Structured Clinical Interview; SCID - 5) were used to determine diagnostic status. Illness severity was evaluated with the Yale-Brown Obsessive Compulsive scale (adapted for MAUD) (Y-BOCS-du) and functional impairment was assessed with the Sheehan Disability Scale (SDS). Histories of exposure and severity of childhood trauma (CT) were measured using the CTQ-SF. Of the 62 participants, 14 (23%) had MAUD and had MAUD+ASPD whereas 48 (77%) had MAUD without ASPD (MAUD-ASPD). Bivariate analyses found significant group differences in terms of gender (df =1) = 8.05; p =< 0.01), language (df = 2) = 7.12; p = 0.03), and level of physical neglect (F(1, 60) = 2.33; M = 9.85; SD = 4.23; p = 0.04). The MAUD+ASPD group members were mostly male (N = 9; 64%), English-speaking and with histories of increased physical neglect. Logistic regression suggested that male gender (beta = 1.08; OR = 8.65; p = 0.01) and English language (beta = 1.55; OR = 11.38; p = 0.03) significantly predicted ASPD comorbidity. There were no significant differences in clinical severity or functional impairment between the MAUD+ASPD and MAUD-ASPD groups. In conclusion, this study indicated that male gender and having English as a first language are associated with MAUD+ASPD but other sociodemographic variables, CT histories and clinical severity and impairment were not. Men who use MA are thus more prone to antisocial behaviour, which complicates their substance use condition. Treatment approaches for MAUD may benefit from developing adaptations that cater for challenges specific to comorbid ASPD. Additionally, the finding regarding first language warrants further investigation. Recommendations for future research are suggested.